POLITIK HUKUM TERHADAP JAMINAN ORANG LANJUT USIA TELANTAR DALAM PERSPEKTIF HAK ASASI MANUSIA BERDASARKAN PASAL 9 DAN 10 UNDANG-UNDANG NOMOR 11 TAHUN 2009 TENTANG KESEJAHTERAAN SOSIAL DI KOTA PEKANBARU - Alfarizi Alfarizi; Emilda Firdaus; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The neglect of the elderly group is still a separate note for the Indonesian state and for local governments. Often we meet this elderly group abandoned alone and very far from a decent life. In fact, according to the mandate of Law Number 10 of 2009 concerning Social Welfare, it really guarantees the poor, neglected orphans and even neglected elderly people without exception. The purpose of writing this thesis: First, to find out the legal politics of the neglected elderly insurance in the perspective of human rights based on Articles 9 and 10 of Law Number 11 Year 2009 concerning Social Welfare in the city of Pekanbaru. Second, to find out the inhibiting factors in the guarantee of neglected elderly people in the perspective of human rights in Pekanbaru City. Third, to find out the efforts that can be made to the Abandoned Elderly Security in the Perspective of Human Rights Based on Articles 9 and 10 of Law Number 11 Year 2009 concerning Social Welfare in Pekanbaru City.The type of research used in this legal research is sociological legal research. The research was conducted in the city of Pekanbaru. Analysis of the data used is the author analyzes the data qualitatively. In drawing conclusions, the writer uses deductive thinking method.From the research results, there are two main things that can be concluded. First, the Legal Politics of Security for Abandoned Elderly Persons in the Perspective of Human Rights Based on Articles 9 and 10 of Law Number 11 Year 2009 concerning Social Welfare in Pekanbaru City, it can be said that it has not run optimally. This is further strengthened by the amount of data obtained by the author, namely as many as 29 neglected elderly groups in the city of Pekanbaru. Second, the inhibiting factors in this case start from the lack of government participation and socialization to directly pay attention to the elderly group, limited human resources in terms of screening the elderly group and the lack of service centers for the elderly in the city of Pekanbaru. Keywords: Legal Politics – Abandoned Elderly – Welfare